2002
DOI: 10.1590/s0066-782x2002000500013
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome da Apnéia Obstrutiva do Sono e sua Relação com a Hipertensão Arterial Sistêmica: Evidências Atuais

Abstract: A síndrome da apnéia obstrutiva do sono é caracterizada pela obstrução completa ou parcial recorrente das vias aéreas superiores durante o sono, resultando em períodos de apnéia, dessaturação de oxihemoglobina e despertares freqüentes com conseqüente sonolência diurna 1 . Os episó-dios de obstrução e apnéia ocorrem em todos os estágios do sono, especialmente no estágio 2 do sono não-REM e durante o sono REM, quando as apnéias tendem a ser mais longas e a dessaturação arterial mais acentuada 2 . Entre os fatore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 67 publications
0
7
0
6
Order By: Relevance
“…[31][32][33] In analyzing the BQ scores, we found that the individuals with obesity participating in the multidisciplinary preoperative preparation program for bariatric surgery at Hospital de Clínicas -Unicamp were at a high risk (80.34%) of developing OSAS, versus 19.66% at low risk, thus confirming that obesity is a disease clearly identified as a risk factor for the development of OSAS. Pinto et al, 34 pointed out controversy as to which are the most significant predictive parameters of obesity leading to this association.…”
Section: Discussionmentioning
confidence: 68%
“…[31][32][33] In analyzing the BQ scores, we found that the individuals with obesity participating in the multidisciplinary preoperative preparation program for bariatric surgery at Hospital de Clínicas -Unicamp were at a high risk (80.34%) of developing OSAS, versus 19.66% at low risk, thus confirming that obesity is a disease clearly identified as a risk factor for the development of OSAS. Pinto et al, 34 pointed out controversy as to which are the most significant predictive parameters of obesity leading to this association.…”
Section: Discussionmentioning
confidence: 68%
“…(8) This obstruction is typically accompanied by decreased oxygen-hemoglobin saturation, and its principal symptoms are loud snoring, periods of apnea, fragmented sleep and frequent awakenings, resulting in daytime sleepiness. (9) One of the principal risk factors for OSAS is body mass index (BMI) greater than 30 kg/m 2 (the cut-off value for obesity as defined by the World Health Organization). (10) Therefore, it could be postulated that the tendency toward excessive daytime sleepiness can be predicted, to some extent, by BMI.…”
Section: Introductionmentioning
confidence: 99%
“…the waist circumference analysis, which was also higher in comparison with ratios observed in the South of Brazil (16)(17) . Although abdominal obesity and obesity itself increase cardiovascular risks, increased waist circumference is associated with obstructive sleep apnea, which results in oxyhemoglobin desaturation episodes, provoking frequent awakening at night and, hence, sleepiness during the day (18)(19) . Studies have demonstrated a positive relation between the presence of obstructive sleep apnea and greater risks of traffic accidents (20)(21) .…”
Section: Resultsmentioning
confidence: 99%